(untitled) (Archives of Clinical and Medical Case Reports, 2019)
Background: CTLA-4 (cytotoxic T-lymphocyte-associated protein 4) deficiency is a widely known cause of immunodeficiency and autoimmunity, determining an immune dysregulation syndrome. We here present the case of a Caucasian woman with common variable immunodeficiency (CVID) and severe enteropathy secondary to CTLA-4 deficiency, successfully treated with abatacept. Case Report: A 54-year-old woman affected by CVID, treated with 20%subcutaneous immunoglobulin, came to our attention for chronic diarrhoea, severe malabsorption and significant weight loss, requiring parenteral nutrition. Her past clinical history comprised psoriatic arthritis, idiopathic thrombocytopenic purpura and multifactorial anemia. She started treatment with glucocorticoids and adalimumab, with partial benefit. However, after six months anti-TNF-alpha agent was withdrawn for recurrent serious infectious episodes. Due to the complex phenotype, we performed a genetic analysis, which revealed the presence of a CTLA-4 heterozygous mutation, with consequent CTLA-4 deficiency. We decided therefore to start abatacept, a CTLA-4 fusion protein, at the dose of 125 mg/week subcutaneously in association with budesonide, with improvement. At one year of follow-up diarrhea is still in remission and the patient has gained weight. Even cutaneous lesions improved, whereas we documented only a partial benefit for peripheral arthritis. Conclusion: CVID could present with complicated phenotype and immune dysregulation, underlying a more complex syndrome, like CTLA-4 deficiency, thus suggesting the importance of genetic investigations in selected patients. Abatacept is a potential effective treatment in patients with documented CTLA-4 deficiency, in particular to induce and maintain remission of enteropathy.